Investigating the Effect of Ramp Geometry on the Flow Characteristics Around Under Pressure Tunnel Aerator Using OpenFoam Open Source Software - Manafpour, M.; Ebrahimnezhadian, H. (Engineering, Technology & Applied Science Research, 2019)
The flow around the ramp embedded in a pressurized tunnel is divided into various zones downstream of the ramp, including the cavity and the main zone of flow above the shear layer. Ramp angle and height are parameters that affect the flow characteristics such as cavity length, velocity, and pressure coefficient immediately downstream of the ramp. In this study, OpenFOAM open source software and RNG K-ε turbulence model were used to simulate the flow around the under pressure tunnel ramp. In order to investigate the effect of the ramp geometry on the flow in various relative air discharges 0<β<10, the range of height and the angle of the ramp as 5<θ<20 and 0.1<tr/d<0.4 were developed and simulated. The correlation coefficient between the numerical and experimental results for the relative cavity length is in the range of 0.9377≤R2≤0.9722 that indicates proper agreement between results. The result of the research shows that in both cases of fixed height of ramp and increasing ramp angle, and fixed angle of the ramp and increasing ramp height, the values of the cavity length and maximum turbulence intensity increase, and the minimum pressure values at the cavity zone bed are decreased. But in both cases, the sensitivity of the three mentioned parameters is higher than the ramp height increment.